New Judgments of the Supreme Court - Oda, Hiroshi (Zeitschrift für Japanisches Recht, 2002)
SHARE OF INHERITANCE BY ILLEGITIMATE CHILDREN The Judgment of the Supreme Court, the Second Petit Bench, March 28, 2003 The Judgment of the Supreme Court, the First Petit Bench, March 31, 2003 PARALLEL IMPORT AND TRADE MARK RIGHT Judgment of the Supreme Court, the First Petit Bench, February 27, 2003 INJUNCTION AGAINST PUBLICATION OF A NOVEL ON THE GROUND OF LIBEL Judgment of the Supreme Court, the Third Petit Bench, September 24, 2002